2019
DOI: 10.1002/slct.201900578
|View full text |Cite
|
Sign up to set email alerts
|

Halogen⋅⋅⋅π Interactions in Supramolecular Architecture of 1D Coordination Polymers and Their Electrical Conductance

Abstract: Two isotypical Cd(II) based one‐dimensional coordination polymers (1D CPs) [Cd2(p‐clba)4(bpy)2]⋅(C2H5OH) (1) and [Cd2(p‐brba)4(bpy)2]⋅(C2H5OH), (2) (H2p‐clba=para‐chlorobenzoic acid, H2p‐brba=para‐bromobenzoic acid and bpy=4,4′‐bipyridine) have been synthesized and characterized by X‐ray structure analysis. In the solid‐state strcuture, both the compounds undergo X⋅⋅⋅п (X=Cl or Br) interactions to generate two‐dimensional (2D) supramolecular architectures. Here, due to the larger size and more polarisability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Although the synthesis of other related systems is required to verify this idea, we think that the enhancement in the electrical conductivity under light irradiation in both devices may be attributed to the donor capacity of π electrons of the Schiff base ligands in 1 and 2 , since both compounds are isostructural. In semiconducting CPs the charge transport mainly depends on the metal–metal distances, the presence of intermolecular interactions, the dimensionality of the CPs, and the nature of the coordinating ligands. , Here the semiconducting behavior depends on the interaction between d orbitals of the metal ions with delocalized π electrons of the organic ligands. The presence of an electron-donating methyl group in L2 vs a H atom in L1 increases the electron density in the aromatic ring and, accordingly, the effective overlap between the d orbitals of the Ni­(II) metal center and the π electrons of the Schiff base ligand in L2.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the synthesis of other related systems is required to verify this idea, we think that the enhancement in the electrical conductivity under light irradiation in both devices may be attributed to the donor capacity of π electrons of the Schiff base ligands in 1 and 2 , since both compounds are isostructural. In semiconducting CPs the charge transport mainly depends on the metal–metal distances, the presence of intermolecular interactions, the dimensionality of the CPs, and the nature of the coordinating ligands. , Here the semiconducting behavior depends on the interaction between d orbitals of the metal ions with delocalized π electrons of the organic ligands. The presence of an electron-donating methyl group in L2 vs a H atom in L1 increases the electron density in the aromatic ring and, accordingly, the effective overlap between the d orbitals of the Ni­(II) metal center and the π electrons of the Schiff base ligand in L2.…”
Section: Resultsmentioning
confidence: 92%
“…The performance of these optoelectronic devices is controlled by a number of factors, which includes electronic band gap, electrical conductivity, charge mobility, surface area, etc. To the best of our knowledge, metamagnetism and optoelectronic properties in a single CP have not yet been reported. In recent times, a few research groups, including ours, have synthesized interesting CPs showing semiconducting properties which are suitable for the application in Schottky devices (Table S1 in the Supporting Information). A close study of these works revealed that most of the post-transition-metal-based CPs exhibiting optoelectronic properties are mainly based on Zn­(II) and Cd­(II). Naskar et al reported three Zn­(II) coordination polymers with electrical conductivities on the order of 10 –4 S m –1 .…”
Section: Introductionmentioning
confidence: 99%
“…The lowering the conductivity is accredited to the insulating nature of the long carbon chain based linker and deprived interaction between the d-orbitals of metal and π-orbitals of ligands. Rational design of thermally and chemically stable CPs promotes their electronic applications. The control of electrical conductance by controlling the molecular structure or molecular assembly is a key issue in molecular electronics. Interestingly, our group is able to project a number of CPs for application in electrical conductivity and device fabrication. …”
Section: Introductionmentioning
confidence: 99%
“…The exploration and synthesis of new one-dimensional coordination polymers based on transition metals and mixed Nand O-donating ligands such as 4,4 0 -bipyridine (4,4 0 -bipy) and benzoate derivatives have been intensively developed (Kaes et al, 2000;Saelim et al, 2020;Topor et al, 2021). The substituent groups at the benzoate ligands play an important role not only for electron densities on the aromatic ring, but also for flexible supramolecular interactions, resulting in various bulk physical properties, such as CO 2 adsorption (Takahashi et al, 2014(Takahashi et al, , 2015, photoluminescence (Lin, 2015) and conductivity (Islam et al, 2019). Among the reported compounds, the majority contain mixed 4,4 0 -bipy and para-substituted benzoate derivatives, but there is a limited number of examples containing meta-substituent benzoate ligands (Fang & Nie, 2011;Kar et al, 2011;Xin-Jian et al, 2013;Lin, 2015).…”
Section: Chemical Contextmentioning
confidence: 99%